Ghana Private Equity and Venture Capital Ecosystem Study - World Bank Group (World Bank, Washington, DC, 2018)
Private equity/venture capital was introduced in Ghana in 1991. In conjunction with this entry of a new asset class, the Government of Ghana (GoG) created a legal/ regulatory framework for VC funds in the early 1990s, regulated by the Bank of Ghana. In late 1991, USAID sponsored a venture capital fund in Ghana, along with the Commonwealth Development Corporation (CDC). The initiative set up two companies, a non-bank finance company to hold the funds, the Ghana Venture Capital Fund (GVCF), and a separate management company, Venture Fund Management Company (VFMC), to make the investments. This initiative created the impetus for legal/regulatory framework for venture capital funds which was defined by the Financial Institutions (Non- Banking) Law of 1993, and “Draft Operating Guidelines for Venture Capital Funding Companies” which were published by the Bank of Ghana in 1995. Ghana is generally touted as an attractive investment destination on the continent because of its stable government and relatively strong business environment. However, there are also some market impediments specific to private equity/venture capital in Ghana. The country’s strong business environment is reflected in its ranking of 70th out of 189 countries in the 2015 World Bank Doing Business Study, above both Kenya (136) and Nigeria (170). However, Treasury bill rates in Ghana have been around 25 percent (91-day and 182-day), making it harder to justify investment in riskier and more illiquid alternative assets by domestic institutional investors. There has been significant depreciation (approximately 75 percent) in the Ghana cedi since the currency was redenominated in 2007 after the significant loss of value of the Second Cedi, which was advanced in 1967. This depreciation in the Ghana cedi has made business fundamentals unsupportive for investment. The objective of this study is to assess the private equity/venture capital (PE/VC) ecosystem in Ghana and to provide recommendations aimed at fostering a robust private equity and venture capital environment that can provide risk financing for competitive small and medium enterprises (SMEs). PE/VC firms are investment managers that mobilize fixed pools of capital to invest in a variety of companies, often across many industries. These firms typically comb the market for high potential investment opportunities through their network of intermediaries, and by developing business linkages and competencies in specific sectors. Apart from providing financing, PE/VC funds tend to take a “capital plus” approach, in that they help the companies in their portfolios to enhance management capacity, improve market focus and presence, strengthen governance, and manage growth. Although PE investment styles may vary considerably, many firms seek financial returns by supporting and financing the growth of the companies in their portfolios. As such, these firms are widely linked to job creation.